The Quality of Colonoscopy Reporting in Usual Practice: Are Endoscopists Reporting Key Data Elements?. (7th August 2016) - Hadlock, S. D.; Liu, N.; Bernstein, M.; Gould, M.; Rabeneck, L.; Ruco, A.; Sutradhar, R.; Tinmouth, J. M.
Abstract : Background . High quality reporting of endoscopic procedures is critical to the implementation of colonoscopy quality assurance programs. Objective . The aim of our research was to (1) determine the quality of colonoscopy (CS) reporting in "usual practice, " (2) identify factors associated with good quality reporting, and (3) compare CS reporting in open-access and non-open-access procedures. Methods . 557 CS reports were randomly selected and assigned a score based on the number of mandatory data elements included in the report. Reports documenting greater than 70% of the mandatory data elements were considered to be of good quality. Physician and procedure factors associated with good quality CS reporting were identified. Results . Variables that were consistently well documented included date of the procedure (99.6%), procedure indication (88.9%), a description of the most proximal anatomical segment reached (98.6%), and documentation of polyp location (97.8%). Approximately 79.4% of the reports were considered to be of good quality. Gastroenterology specialty, lower annual CS volume, and fewer years in practice were associated with good quality reporting. Discussion . CS reporting in usual practice in Ontario lacks quality in several areas. Almost 1 in 5 reports was of poor quality in our study. Conclusions . Targeted interventions and/or use of mandatory fields in synoptic reports should be considered to improve CS reporting.